Faith-Based Intervention: Prison, Prayer, and Perseverance - Robinson-Edwards, Shona (Religions, 2018)
This qualitative article explores the impact of faith-based interventions through the lens of a self-identified practicing Christian: Joanna. For over a decade, Joanna has visited several prisons in the United Kingdom in a faith-based capacity: supporting prisoners, families, and prison chaplaincies. Joanna professes the role of faith and religiosity to be a positive and influential component in the lives of those imprisoned. This paper explores Joanna's journey of supporting individuals within the prison walls, reflecting on the impact of labels, imprisonment, faith-based intervention, and religiosity. Much of the current research pertaining to faith-based interventions are limited; therefore, the experiences of those who volunteer within prisons in a faith-based capacity is often overlooked. Yet, faith-based intervention and religiosity within a criminal justice context provides several benefits which impact on those in prison, their families, and people working within a prison environment.